La actual narrativa infantil y juvenil española - Vásquez Vargas, Magdalena (Universidad de Costa Rica, 2006)
This article approaches the Spanish development in children's and youth narrative literature development after the Civil War. It shows a wide view of the most representative literary pieces and authors. It mainly highlights the features of the narrative produced in the democratic regimen reestablishment period.